Is Bt Gene Cotton Adoption Paying Off Farmers in Pakistan? - Mansoor, Sadia; Bashir, Sobia; Zubair, Muhammad (Asian Development Policy Review, 2020)
Existing literature on impact of Bacillus Thuringiensis (Bt) cotton gene adoption in Pakistan is based on districts of one province and one or two years of data. This study contributes to literature in two aspects; we have conducted farm level survey in six districts (Rahim Yar Khan, Multan, Bahawalpur, Matiari, Shaheed Benazirabad and Sukkur) of two provinces (Punjab and Sindh) of Pakistan for three consecutive years (2014-15 to 2016-17) to assess the comparative advantage of Bt gene adoption over conventional cotton crop within and across provinces. Moreover, this study has assessed farmer’s wellbeing by comparing per capita income of farmers with poverty line. Results of panel data indicate that net yield gain from Bt gene cotton per acre is 33 to 37.5 % higher than conventional cotton gene. However, Bt cotton yield per acre is 13% higher in districts of Punjab than yield in districts of Sindh, this has resulted in huge gap between per capita incomes of Bt farmers in these provinces. Furthermore, Bt gene growers have significantly low pesticide applications as compared to conventional cotton producers. The results obtained from Cobb-Douglas production specification establish that irrigation cost, seed cost and fertilizer quantity have significant positive impact on over all cotton yield. This study suggests that awareness programs regarding refuge area and specification of seeds might improve yield as well as per capita income of farmers in Pakistan.